If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=4(-2x+5)=-6x+3
We move all terms to the left:
3-(4(-2x+5))=0
We calculate terms in parentheses: -(4(-2x+5)), so:We get rid of parentheses
4(-2x+5)
We multiply parentheses
-8x+20
Back to the equation:
-(-8x+20)
8x-20+3=0
We add all the numbers together, and all the variables
8x-17=0
We move all terms containing x to the left, all other terms to the right
8x=17
x=17/8
x=2+1/8
| 12+5x-5=8x+8-5x | | -4x+5x-1=0 | | 3b+2b=7 | | -3x–7=-25, | | 5x=91-2 | | 3(2x-5)-4x=3 | | 51=5-12s | | 3+6x+7x=48 | | 2r-6=9-r | | -7(-3x-6)=63 | | n/13=-1 | | n^2=-60+16n | | 132=2x+54 | | 6n+9=(−3n)−21−6 | | 1+2(x-5)=5-2(x-2) | | 132=x-54 | | 5x+7=-3x+15 | | 4-(9x+4)=3-x | | 2x-4=-3x-4 | | 70=5w+14 | | 8p^2-8p=12 | | 2x+8x=+8 | | 5x+27=4x+33 | | ∠A=6x+5∘ | | 3^(3r)=81 | | 3^3r=81 | | 5(y+6)=-2(5y-6)+7y | | 2.2x+.8x-5=4x | | 2n-8=n+n-4-4 | | 6(-7x-1)=-300 | | 2(-1x+2)=-14 | | 4w-2+4(2w+4)=-2(w+1) |